Study on Correlations Among PAHs and SPM During Crop Residue Burning Events at a Semi-Urban Site of Patiala - Ritika, Arora (My University, 2014)
Burning agriculture waste has long been practiced to prepare land for planting, saving time in clearing the land for the next crop, return nutrients to the soil, increase harvests and control pests, etc. These burning events of wheat and rice crop residues after harvesting of respective crops are important contributors to the higher concentration levels of suspended particulate matter (SPM) in the ambient air of Punjab. Besides being career of other pollutants, these are vehicles of unburnt hydrocarbons including polycyclic aromatic hydrocarbons (PAHs). A study was done to analyze aerosol samples collected previously using high volume sampler with GMF/A sheets for 24h period at Thapar University Campus (TUC) site of Patiala, Punjab. After extraction of all the samples with dichloromethane, each sample was injected in Gas chromatograph fitted with stainless steel capillary column (dimethyl polysiloxane). The four PAHs namely pyrene, benzo(a)anthracene, chrysene, benzo(b)fluoranthene were identified as these are the four compounds observed frequently throughout the study. The concentration levels of individual PAH compound varied from 0.36 to 625 μgm-3with mean value of total PAH concentration (TPAH) of 275+161 μgm-3. In the present study, concentration levels of each one of these have been correlated with respective concentration levels of TSPM in the ambient air of TUC. A seasonal trend was observed for both SPM and the PAH concentration. Concentration of PAH varied inversely with temperature. Hence, the situation of ambient air quality during the months of October and November is much worse than that in the months of April and May. The reason for sharp increase in PAH content in Oct-Nov is that the stubble burning after rice crop harvesting happens at much lower temperature and in more humid environment as compared to that in April and May when the dry stubble burns quickly in the peak summer season. Low ambient temperature results in relatively incomplete burning hence leads to more soot formation.
MT, SEE
Keywords: Crop residues; SPM; PAH; Urban